Testosterone, Thrombophilia, and Thrombosis. (January 2014) - Glueck, Charles J.; Richardson-Royer, Caitlin; Schultz, Reiker; Burger, Tim; Labitue, Fanta; Riaz, Muhammad K.; Padda, Jagjit; Bowe, Dedrick; Goldenberg, Naila; Wang, Ping
We describe thrombosis, deep venous thrombosis (DVT) pulmonary embolism (PE; n = 9) and hip-knee osteonecrosis (n = 5) that developed after testosterone therapy (median 11 months) in 14 previously healthy patients (13 men and 1 woman; 13 Caucasian and 1 African American), with no antecedent thrombosis and previously undiagnosed thrombophilia–hypofibrinolysis. Of the 14 patients, 3 were found to be factor V Leiden heterozygotes, 3 had high factor VIII, 3 had plasminogen activator inhibitor 1 4G4G homozygosity, 2 had high factor XI, 2 had high homocysteine, 1 had low antithrombin III, 1 had the lupus anticoagulant, 1 had high anticardiolipin antibody Immunoglobulin G, and 1 had no clotting abnormalities. In 4 men with thrombophilia, DVT-PE recurred when testosterone was continued despite therapeutic international normalized ratio on warfarin. In 60 men on testosterone, 20 (33%) had high estradiol (E2 >42.6 pg/mL). When exogenous testosterone is aromatized to E2, and E2-induced thrombophilia is superimposed on thrombophilia–hypofibrinolysis, thrombosis occurs. The DVT-PE and osteonecrosis after starting testosterone are associated with previously undiagnosed thrombophilia–hypofibrinolysis. Thrombophilia should be ruled out before administration of exogenous testosterone.